Suppliers' Capability-Building in Public Procurement of Innovation - Ali Bonyadi Naeini; Ali Maleki; Najmoddin Yazdi (سیاست نامه علم و فناوری, 2021)
PPI is an innovation policy that industrialized countries have studied since the early twenty-first century because to the large contribution of government purchases to their national economies. Despite its attraction, this demand-side innovation policy has failed to capture the attention of emerging and less developed countries, owing to their demands and circumstances being distinct from those of developed ones. One of these conditions is insufficient supplier capability. This review paper examined 1) the theoretical underpinnings of supplier capability development and public procurement of innovation, 2) the body of existing research, and 3) conducted an introductory scientometric analysis of these two literatures. The findings indicated that both fields are burdened by a small number of publications that are largely unrelated to one another. Developed countries have viewed this topic as a secondary goal of PPI policy, which develops organically during this policy - most likely because suppliers' capability building is not their primary objective in comparison to the growth of innovation. Developing countries, on the other hand, require purposeful targeting of this objective in order to leverage public procurement.